Baha’faridism Between reform of zoroastrianism and opposition to Islam - Ismail, Farsat M. (Humanities Journal of University of Zakho, 2013)
In the vision of the majority of the old and contemporary Muslim historians Bahfred is considered one of the Persian opposition movements against the Islamic caliphate in its both omian and Abbasside parts. This study comes out of an other prospective, that this movement is reckoned one of the reform moves that targeted zarodost religion because Bahafred felt the people needs who belong to the magician religion = definitely zarodost to keep its basic principles where danger was threatening it due to the spreading of the Islamic religion in those region broadly . Disorder ((tumuit)) of the political situation in addition to dominance of provocation in the eastern regions = kharasan and beyond river land. Bahfred is considered in the vision of the majority of the historians .